The river is waiting : a novel - Lamb, Wally (Marysue Rucci Books, 2025)
"From the New York Times bestselling author of Oprah Bookclub Picks I Know This Much Is True and She's Come Undone comes the heart wrenching story of a young father who, after an unbearable tragedy, reckons with the possibility of atonement for the unforgivable"--